Intervensi behavioral berbasis sekolah pada anak selective mutism: Penerapan stimulus fading dan prompting - Fitriana Widyastuti (Universitas Sarjanawiyata Tamansiswa, 2020)
Abstract. Children with selective mutism have persistent failure to speak in certain social situations that expect them to speak. It is can affect academic performance, social relations, and lead to the development of more serious psychological disorders. Based on these conditions, necessary to reduce the symptoms of selective mutism with an intervention program. This study used a behavioral intervention with fading and prompting in a school setting. This intervention involves the collaboration of teachers and parents. The study was conducted with a single case experimental study on subjects aged 4 years who were indicated selective mutism symptoms. An observation, interviews, and the Selective Mutism Questionnaire (SMQ) used as diagnostic and examination tools. The results showed that the provision of intervention with fading and prompting stimulus techniques had a significant effect on increasing speaking and social interaction of selective mutism child.Key words: selective mutism, stimulus fading, prompting, selective mutism, parents-school collaboration